2012
DOI: 10.1186/1471-2229-12-106
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the MYB transcription factor superfamily in soybean

Abstract: BackgroundThe MYB superfamily constitutes one of the most abundant groups of transcription factors described in plants. Nevertheless, their functions appear to be highly diverse and remain rather unclear. To date, no genome-wide characterization of this gene family has been conducted in a legume species. Here we report the first genome-wide analysis of the whole MYB superfamily in a legume species, soybean (Glycine max), including the gene structures, phylogeny, chromosome locations, conserved motifs, and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
302
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(339 citation statements)
references
References 83 publications
32
302
1
4
Order By: Relevance
“…The Populus genome contains five 3R-MYB genes and 192 R2R3-MYB genes (Wilkins et al 2009). A total of 252 MYBs, including 244 R2R-MYB (2R-MYB) genes, six R1R2R3-MYB (3R-MYB) genes, and two R0R1R2R3-MYB (4R-MYB) genes were identified in soybean (Du et al 2012b). Supriya et al (2006) and Sharma et al (2010) reported MYB TF in Brassica species.…”
Section: Myb Transcription Factormentioning
confidence: 99%
“…The Populus genome contains five 3R-MYB genes and 192 R2R3-MYB genes (Wilkins et al 2009). A total of 252 MYBs, including 244 R2R-MYB (2R-MYB) genes, six R1R2R3-MYB (3R-MYB) genes, and two R0R1R2R3-MYB (4R-MYB) genes were identified in soybean (Du et al 2012b). Supriya et al (2006) and Sharma et al (2010) reported MYB TF in Brassica species.…”
Section: Myb Transcription Factormentioning
confidence: 99%
“…In this study, we focused on one of the MYB-related genes, Ljmybr, which is expressed after M. loti infection. Although there are many reports about R2R3-MYB proteins, little is known about MYB-related genes (Du et al 2012a;Du et al 2012b;Matus et al 2008;Stracke et al 2001). In maize and soybean, MYB-related genes have roles both in development and in stress responses (Du et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Após o agrupamento e a designação dos subgrupos, motivos foram detectados na poção C-terminal das sequências utilizando o software MEME 1 . 1,3,6 . Observou-se ainda subgrupos formados exclusivamente por AtMYBs, indicando a ausência de controle sobre determinadas funções por MYBs em soja (S5; S12 e S15).…”
Section: Introductionunclassified